Kajian Capaian Program Mahasiswa Wirausaha - Hartono Hartono (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2018)
Student Entrepreneur Program ( PMW Program ) conducted since 2009 need to be evaluated it’s achievement so that the improvement can be arranged. The aspect evaluation is stressed on changed of attiude, paradigm, and committment of student in entrepreneur profession. The population of this research is student participated PMW program from all of politechnic , university, and high school arroud Indonesia. Respondent was elected by purposive random sampling i.e that assumed the best because of being delegation of their politechnic in KMI expo on 2016 that held by Brawijaya Unversity Malang.The data was collected by questionaire that designed for explore and identify the tendency student being serious and commit on entrepreneur profession. Data processing result that 99% respondent believe in prospective entrepreneur profession so that better to start business since study in campus ( 81% ) althought they faced dilemma of academic obligation ( 64% ). They still believed that the main factor of entrepreneur is money as capital ( 76% ) , however this statement was supported by the fact that 92% respondent confession that their participation on PMW program because of start up fund. The committment on entrepreneur become nonsense because majority of partipant would seek a job when finished their study and would start business if do not getting job yet.